MKK7 deficiency in mature neurons impairs parental behavior in mice. (18th November 2020) - Shin, Tadashi; Hiraoka, Yuichi; Yamasaki, Tokiwa; Marth, Jamey D.; Penninger, Josef M.; Kanai‐Azuma, Masami; Tanaka, Kohichi; Kofuji, Satoshi; Nishina, Hiroshi
Abstract: c‐Jun N‐terminal kinases (JNKs) are constitutively activated in mammalian brains and are indispensable for their development and neural functions. MKK7 is an upstream activator of all JNKs. However, whether the common JNK signaling pathway regulates the brain's control of social behavior remains unclear. Here, we show that female mice in which Mkk7 is deleted specifically in mature neurons ( Mkk7 flox/flox Syn‐Cre mice) give birth to a normal number of pups but fail to raise them due to a defect in pup retrieval. To explore the mechanism underlying this abnormality, we performed comprehensive behavioral tests. Mkk7 flox/flox Syn‐Cre mice showed normal locomotor functions and cognitive ability but exhibited depression‐like behavior. cDNA microarray analysis of mutant brain revealed an altered gene expression pattern. Quantitative RT‐PCR analysis demonstrated that mRNA expression levels of genes related to neural signaling pathways and a calcium channel were significantly different from controls. In addition, loss of neural MKK7 had unexpected regulatory effects on gene expression patterns in oligodendrocytes. These findings indicate that MKK7 has an important role in regulating the gene expression patterns responsible for promoting normal social behavior and staving off depression. Abstract : c‐Jun N‐terminal kinase (JNK) signaling has well established, important roles in mammalian brain development and neural functions. However, whether the mitogen‐activated protein kinase kinase 7 (MKK7), a specific upstream activator of JNK, regulates social behavior remains unclear. In this study, we demonstrate that the MKK7‐JNK pathway in mature neurons regulates mouse mental status and plays a critical role in parental behavior.